FENOMENA HOMOSEKSUAL DALAM NOVEL INDONESIA MUTAKHIR - -, Wiyatmi (Diksi, 2007)
his research is aimed at describing and understanding (1) homosexualityphenomena in the current Indonesian novels, (2) the relationship betweenhomosexuality phenomena with existences of homosexual community inIndonesia., (3) the relationship between homosexuality phenomena with feministschool.To achieve the aims, six novels are analyzed. Those are (1) Larung by AyuUtami, (2) Supernova by Dee (Dewi) Lestari, (3) Mahadewi Mahadewi (4) GarisTepi Seorang Lesbian by Herlinatien, (5) Tabularasa by Ratih Kumala, and (6)Dadaisme by Dewi Sartika.The result of the research shows that (1) the homosexualityphenomena in the current Indonesian novels reflected in theme and characterproblems, (2) this phenomena is related with existences of homosexualcommunity in Indonesia, whom already demmad their existebce in society, and (3)this phenomena is related to feminism, especially radical feminism that influencedin authors creativity.Key word: homosexual, Indonesia novels, feminism